International Calvinism and the Reformed church of Hungary and Transylvania, 1613-1658 - Murdock, G; Murdock, Graeme (1996)
﻿ The Reformed church in Hungary and Transylvania had extensive connections with western Calvinist churches during the early seventeenth century, and became more closely linked with co-religionists abroad during this period. In this thesis I shall examine the ideology and shared interests of this international Calvinist community, and assess the significant impact which contacts with fellow Calvinists beyond Hungary's borders had on the development of the Hungarian Reformed church. The early seventeenth century saw increasing numbers of Hungarian student ministers travel to western Reformed universities, western Calvinist teachers travel to work in Hungarian schools, and the transfer and translation of foreign Reformed theological works for use in Hungary and Transylvania. This pattern of broad engagement with western Europe heavily influenced the development of education in the Reformed schools of Hungary and Transylvania, as well as the forms of worship and ceremony adopted by the Hungarian Reformed church. Godly princes, godly gentlemen and clergy were partners in the building-up of the Reformed church of Hungary and Transylvania. The church was indeed reliant in the early seventeenth century on patronage and support from a series of Reformed Transylvanian princes, and from Hungarian nobles. The continuing commitment of these parties to further religious reformation in the region was challenged by some Reformed ministers who, inspired by their experience of Calvinist churches abroad, sought to introduce presbyterial government and reforms of church ceremony and discipline, an agenda dubbed locally as Puritanism. International Calvinist contacts however largely served to bolster the theological orthodoxy of the Reformed community of Hungary and Transylvania against its confessional rivals, invigorating the Reformed church's zeal to defend its position with a stridently anti-Catholic ideology. Comparisons with other Reformed churches reinforced commitment in Hungary to tighten standards of discipline with an ethos of morality which was distinctively Reformed. International Calvinism therefore assisted the Reformed confessionalisation of Transylvania and eastern Hungary in the early seventeenth century. However the ties binding Transylvania with the rest of the Calvinist world in this period also encouraged Transylvania's princes to adopt a diplomatic policy of Protestant cooperation tinged with apocalyptic ideas, which was ultimately to jeopardise the stability of the principality and the place of Reformed religion in east-central Europe.